Decreased Functional Connectivity of the Primary Visual Cortex and the Correlation With Clinical Features in Patients With Intermittent Exotropia - He, Xueying; Hong, Jie; Liu, Zhaohui; Wang, Qian; Li, Ting; Qu, Xiaoxia; Fei, Nanxi; Li, Wei; Fu, Jing (Frontiers in Neurology, 2021)
The purpose of this study is to investigate characteristic alterations of functional connectivity (FC) patterns in the primary visual area (V1) in patients with intermittent exotropia (IXT) using resting-state functional magnetic resonance imaging (rs-fMRI) and how they relate to clinical features. Twenty-six IXT patients and 21 age-, sex-, handedness-, and education-matched healthy controls (HC) underwent rs-fMRI. We performed FC analyses between bilateral V1 and other brain areas and compared FC strength between two groups. A Pearson correlation analysis was used to evaluate the correlation between the FC differences and clinical features. Compared with HCs, patients with IXT showed significantly lower FC of the right V1 with the right calcarine sulcus and right superior occipital gyrus, and the left V1 with bilateral cuneus and right postcentral gyrus. The Newcastle Control Test score was positively correlated with mean FC values between the left inferior parietal lobule and bilateral V1, and between the left supramarginal gyrus and left V1. The duration of IXT was positively correlated with mean FC values between the right inferior occipital gyrus and right V1. Reduced FC between the V1 and various brain regions involved in vision and eye movement processes may be associated with the underlying neural mechanisms of impaired visual function in patients with IXT.